PASSIVE IRRIGATION SYSTEM FOR GREEN ROOFS - George MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper present an innovative system for green roof irrigation. This is based on natural flow of water through plants witch mean capillarity. The system work in two directions: collecting the rain water in suspended tanks on the top of the building, under growing substrate and then transporting the water through capillary conductor, watering the substrate. This solution can be applied on large scale for all constructions witch wont to convert their roofs to green roofs.